When diet is not enough - obesity treatment options - Polatowska, Marika; Czudy, Zuzanna; Dominik, Hanna; Pawęska, Wojciech; Radwański, Jan; Gadomska, Anna; Kurek, Justyna; Gorzyński, Rafał; Garstka, Michał; Molczyk-Sieńczak, Justyna (Journal of Education, Health and Sport, 2023)
Introduction: Obesity and overweight are common diseases affecting both children and adults. They cause a number of health consequences, both physical and mental. The diseases underlying obesity include hypertension, type II diabetes and selected cancers. The etiology is multifactorial, resulting from environmental, behavioral and genetic factors. Aim of the study: The aim of our study is to summarize the therapeutic options available to overweight and obese people. We paid special attention to the available pharmacology and surgical treatment. We compared these methods in terms of effectiveness, possible complications and side effects. Materials and methods: The literature available in the PubMed and Google Scholar databases was reviewed, using the following keywords: "obesity treatment", "obesity pharmacotherapy", "bariatric surgery". Conclusions: There are many treatment options for people who have not improved with diet and increased physical activity alone. The availability of both pharmacotherapy and bariatric surgery enables effective treatment of obesity and overweight tailored to the needs of patients.